Chemical composition and insecticidal efficacy of two animals’ horn and hoof crude extracts against lesser grains borer, Rhyzopertha dominica (F.) [Coleoptera: Bostrichidae] - Kayode David Ileke; Catherine Olukemi Adeniran (Heliyon)
This research evaluated the profiling of bioactive compounds and insecticidal activities of the crude extracts of horns and hoofs of cow and goat against Rhyzoperta dominica on wheat grains. Different concentrations (0.1, 0.2, 0.3, 0.4 and 0.5 ml) of the crude extracts were applied per 20 g of wheat grains to assess the toxicity effect on adult mortality and adult emergence. The different concentrations of the two extracts evoked mortality of R. dominica. However, the most effective concentration was 0.5 ml of the crude extract of goat horn causing 100 % mortality after 5days of application, while extract of cow hoof at the same concentration resulted in 86.67 % mortality of R. dominica after 5 days of exposure. The required lethal concentration needed to control 50 % population of R. dominica by extract of cow horn and goat hoof after 24 h exposure was 0.57 ml and 0.48 ml, respectively. Proximate compositions of the animal hoofs and horns showed that the samples contained fat, crude protein and ash. The number of bioactive compounds detected in cow hoof was 44 and goat horn was 21. The study has shown the insecticidal potential of the understudied animal materials. The use of extracts from the horns of goats should be looked into and explored as an eco-friendly measure in the control of R. dominica.